Rare element minerals’ assemblage in El Quemado pegmatites (Argentina): insights for pegmatite melt evolution from gahnite, columbite-group minerals and tourmaline chemistry and implications for minerogenesis - López, Vanina Lucrecia (2021)
The pegmatite district of El Quemado (NW Pampean Ranges, NW Argentina) hosts several Ordovician pegmatite bodies of theLCT (Li, Cs, Ta) type. We present paragenetic assemblages for a set of samples from two of the El Quemado pegmatite groups,Santa Elena and Tres Tetas, and mineral chemistry analyses for gahnite, columbite-group minerals, tourmaline, micas, albite,microcline, and discuss the relation between their major element composition and the degree of evolution of pegmatite melts. Thechemical composition of rare element minerals allows recognizing an evolutive trend reaching highly differentiated compositions, with complex paragenetic assemblages including Li-, Zr-, U-, Zn-, P-, Mn- and Ta-bearing minerals. The temperature ofcrystallization during the magmatic phase was below 400 °C. Non-pervasive hydrothermal alteration, testified by a moderatepresence of phyllosilicates, affected the pegmatite bodies. Chlorite geothermometry indicates that the circulation of postmagmatic hydrothermal fluids occurred at a temperature ranging between 200 °C and 250 °C. The mineralogical featuresrecognized in the El Quemado pegmatite rocks have implications for the metallogenesis of the region, suggesting that thepegmatites potentially contributed to the genesis of Ta-Nb oxide placer mineralizations.